Determination of P, Mg, Al and Fe in Phosphate Ores by Inductively Coupled Plasma-Atomic Emission Spectrometry - WU Ying-chun; YUE Yu-chao; NIE Feng (Yankuang ceshi, 2014)
The traditional method for determining multiple elements in phosphate ores is to decompose the phosphate ore samples with a mixture of HNO3, HCl and HF, and take measurements using Inductively Coupled Plasma-Atomic Emission Spectrometry (ICP-AES). The addition of HF thoroughly decomposes silicates in which the target elements are found. However, the process of HF removal is very complicated. A rapid sample processing method has been determined to simplify the method. If only four elements of P, Mg, Al and Fe need to be determined, the addition of HF is unnecessary, which may be related to a small amount of HF introduced during the samples processing by HNO3 and HCl. In order to verify the decomposition capacity of the mixed acids, phosphate ores samples were decomposed in a conical flask with mixed acids of HNO3 and HCl (HNO3:HCl=1:1) without HF, and dissolved with dilute acid solution, then the sample solution was determined directly by inductively coupled plasma-atomic emission spectrometry. Analysis results show that there is no significant impact on the results of P, Mg, Al and Fe, and the detection limits of the method were 100 μg/g (P), 0.3 μg/g (Mg), 20 μg/g (Al) and 6 μg/g (Fe), respectively. The presented method has been applied to the determination of P, Mg, Al and Fe in the national standard reference materials. The results show that the determination precision (RSD) is better than 5% (n=12) and the relative error is less than 1.5%. The method has advantages of high accuracy, simplicity and rapidity, and can meet the demands of practical analysis for phosphate ores without Ca and Si elements.